Mechanical tolerance stackup and analysis - Fischer, Bryan R., 1960- (Boca Raton, FL : CRC Press, 2011)
'Written by one of the foremost authorities in the field, Mechanical Tolerance Stackup and Analysis presents proven and easy-to-use methods for determining whether selected dimensioning and tolerancing schemes will yield functional parts and assemblies and the most practical procedure to communicate the results. Using a variety of examples and real-world design challenges that stress the importance of a standardized approach to tolerance stackups, the book helps readers develop effective problem-solving and analytical skills. Demonstrates how to perform'what-if' scenarios to evaluate the effects of changing tolerancing schemes, tolerance values, and assembly sequences. Mechanical Tolerance Stackup and Analysis is an outstanding and must-have reference for all mechanical, manufacturing, design, quality control, project, process, industrial, automation, and assembly engineers and managers; and upper-level undergraduate, graduate, and continuing-education students in these disciplines'--
'Written by one of the foremost authorities in the field, this reference presents proven and easy-to-use methods for determining whether selected dimensioning and tolerancing schemes will yield functional parts and assemblies. The book develops effective problem-solving and analytical skills using a variety of examples and real-world design challenges that stress the importance of a standardized approach to tolerance stackups. Illustrating procedures that have been tested and utilized by leading professionals in the industry, this reference demonstrates how to perform'what-if' scenarios to evaluate the effects of changing tolerancing schemes, tolerance values, and assembly sequences'--
Includes index.
'Written by one of the foremost authorities in the field, Mechanical Tolerance Stackup and Analysis presents proven and easy-to-use methods for determining whether selected dimensioning and tolerancing schemes will yield functional parts and assemblies and the most practical procedure to communicate the results. Using a variety of examples and real-world design challenges that stress the importance of a standardized approach to tolerance stackups, the book helps readers develop effective problem-solving and analytical skills. Demonstrates how to perform'what-if' scenarios to evaluate the effects of changing tolerancing schemes, tolerance values, and assembly sequences. Mechanical Tolerance Stackup and Analysis is an outstanding and must-have reference for all mechanical, manufacturing, design, quality control, project, process, industrial, automation, and assembly engineers and managers; and upper-level undergraduate, graduate, and continuing-education students in these disciplines'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Tolerance (Engineering)